2015
DOI: 10.1016/j.iccn.2014.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of position and operator on high-frequency ultrasound scan quality

Abstract: Objectives High-frequency ultrasound may evaluate those at risk for pressure ulcers. Images may be obtained by clinicians with limited training. The prone position is recommended for obtaining sacral scans but may not be feasible in the critically ill. This study investigated image quality using multiple operators and a variety of patient positions. Research Methodology Sacral scans were performed in three randomized positions in 50 volunteers by three different investigators using a 20 MHz ultrasound system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Our previous study evaluated the quality of images obtained by multiple operators in different subject positions (prone, left side-lying with 60 degree rotation, left side-lying with 90 degree rotation) and found that the overall scan quality was similar in all positions with all operators. 22 …”
Section: Key Variables and Their Measurementmentioning
confidence: 99%
“…Our previous study evaluated the quality of images obtained by multiple operators in different subject positions (prone, left side-lying with 60 degree rotation, left side-lying with 90 degree rotation) and found that the overall scan quality was similar in all positions with all operators. 22 …”
Section: Key Variables and Their Measurementmentioning
confidence: 99%
“…In our recent study evaluating general HFUS thickness and density measurements between prone, 60 degree, and 90 degree side-lying positions, we found significant differences between thickness and density with respect to position. 16 Specifically layer thickness and density were significantly less for the prone position than either the 90 degree or 60 degree positions. Due to significant differences found with respect to position for thickness and median intensity, we further report LEP:TP ratio for all three positions.…”
Section: Methodsmentioning
confidence: 83%
“…As is well-known, highest quality scans produce highest quality data although we showed that high quality scans are not always possible. 16 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations